ENHANCING ENGLISH PROFICIENCY THROUGH IMMERSIVE LEARNING - Aini, Qurrotul; Asan, Nassuha (Faculty of Letters Universitas Abdurachman Saleh Situbondo, 2025)
The International Community Service Program (KKN) at Darul Furqon School in Narathiwat, Thailand, aimed to enhance the English language skills of senior high school students through two main activities: teaching English at school and conducting an